Potential Antifungal Targets Based on Glucose Metabolism Pathways of Candida albicans - Chen, Xueqi; Zhang, Zewen; Chen, Zuozhong; Li, Yiman; Su, Shan; Sun, Shujuan (Frontiers in Microbiology, 2020)
In recent years, fungal infections have become a serious health problem. Candida albicans (C. albicans) are considered as the 4th most common isolates associated with approximately 40% mortality in bloodstream infections among hospitalized patients. Due to various limitations of classical antifungals used currently, such as limited kinds of drugs, inevitable toxicities and high price, there is an urgent need to explore new antifungal agents based on novel targets. Generally, nutrient metabolism is involved with fungal virulence, glucose is one of the important nutrients in C. albicans. C. albicans can obtain and metabolize glucose through a variety of pathways, in theory, many enzymes in these pathways can be potential targets for developing new antifungal agents, and several studies have confirmed that compounds which interfere with alpha-glucosidase, acid trehalase, trehalose-6-phosphate synthase, class II fructose bisphosphate aldolases and glucosamine-6-phosphate synthase in these pathways do have antifungal activities. In this review, the glucose metabolism pathways in C. albicans, the potential antifungal targets based on these pathways, and some compounds which have antifungal activities by inhibiting several enzymes in these pathways are summarized. We believe that our review will be helpful to the exploration of new antifungal drugs with novel antifungal targets.